CoOx(OH)2(1-x) doped with Sn urchin-like spheres for enhanced oxygen evolution reaction. (May 2020) - Sun, Lina; Han, Cong; Zhang, Ting; Zhu, Huixia; Xia, Xiaohong; Li, Ling
Abstract: Designing an efficient and stable electrocatalyst is key for the enhanced oxygen evolution reaction. This paper proposes a hydrothermal method for synthesising Sn-doped CoOx (OH)2(1-x) (CoOx (OH)2(1-x) -Sn(Ⅳ)). During the preparation process, the morphology of the precursor was controlled by an anionic surfactant. The precursor of the layered structure was mainly formed through the bonding of anionic group SO3 H − in SDBS with metal cation Co 2+, and the surface area and reaction sites of the precursor were clearly increased. Finally, CoOx (OH)2(1-x) -Sn(Ⅳ) urchin-like spheres were hydrothermally synthesised. The current density of the CoOx (OH)2(1-x) -Sn(Ⅳ) obtained at a potential of 1.95 V was 124.8 mA cm −2, i.e. 2.8 times higher than that of the precursor (44.9 mA cm −2 ). The Tafel slope of the precursor was 156.1 mV dec −1, i.e. 3.3 times that of CoOx (OH)2(1-x) -Sn(Ⅳ) (48.0 mV dec −1 ).